The Protection Of Women As The Victim Of Economic Abuse Under International Human Rights Law In Indonesia - Rayyan Fakhri; Azhari Yahya (Jurnal Ilmiah Mahasiswa Bidang Hukum Keperdataan, 2019)
ndonesia is included as a state which already ratified the Convention on the Elimination of Discrimination Against Women (CEDAW) 1979. Those matters oblige Indonesian governments to give full protection to women regarding to crimes of violence. However, it also includes protection to the victim of economic abuse in family scope. The annual report of Women Commission show that economic abuse on family scope is always happen in every year. Article 9 of Law No 23 of 2004 on the Elimination of Domestic violence regulated economic abuse as a form of domestic violence. The aim of this research is to describe the protections of economic rights for women covered by International Human Rights Law in Indonesia and to describe the responsibility of Indonesian government to protect women as the victim of economic abuse.This research is conducted under normative method. The data used in this research comes from primary sources such as statutes, Law, decision, or regulation and secondary sources, which includes legal textbook, papers and journals. Both sources then combined with tertiary sources, such as dictionary. Indonesian stipulated the equality and nondiscrimination on women’s economic rights under the 1945 Constitution, Law No. 39 of 1999 on Human Rights, the Law No.13 of 2003 on Labor and Law No. 1 of 1974 on Marriage. In term of avoiding economic abuse in family scope Indonesian government also established the Law No. 23 of 2004 on the Elimination on Domestic Violence. The article found that one of the biggest problems is the need of women’s victim protection when they made the report on the economic abuse cases. Domestic Violence Law has been provided the protection and recovery towards the victim of economic abuse. Furthermore, Indonesia Government has also established National Commission on Violence against Women to help the women’s victim acquire their rights. In the provincial/district level, Integrated Services Center for Women and Children was established in each area. Local and provincial efforts are the key solution on the enforcement issue. The government whether national, provincial, and regional has to socialize the economic abuse and women’s economic rights to make sure that they are aware on their rights. The evaluation towards the implementation of law No. 23 of 2004 on the Elimination of Domestic Violence is needed to know how the efficiency of this law.